Migration and modernities : the state of being stateless, 1750-1850 - DeLucia, JoEllen; Shields, Juliet, 1976- (Edinburgh scholarship online., 2019)
This collection initiates transnational, transcultural and interdisciplinary conversations about migration in the 18th and 19th centuries.